Investigating Employee-Reported Benefits of Participation in a Comprehensive Australian Workplace Health Promotion Program. Issue 5 (May 2016) - Kilpatrick, Michelle; Blizzard, Leigh; Sanderson, Kristy; Teale, Brook; Nelson, Mark; Chappell, Kate; Venn, Alison
Abstract : Objective: To investigate employee-reported benefits of participation, employee organizational commitment, and health-related behaviors and body mass index (BMI) following implementation of a comprehensive workplace health promotion (WHP) program. Methods: State government employees from Tasmania, Australia, completed surveys in 2010 ( n  = 3408) and 2013 ( n  = 3228). Repeated cross-sectional data were collected on sociodemographic, health, and work characteristics. Participation in WHP activities, employee-reported organizational commitment, and benefits of participation were collected in 2013. Results: Respondents who participated in multiple activities were more likely to agree that participation had motivated them, or helped them to address a range of health and work factors (trends: P  < 0.05). There were significant associations between participation and employee organizational commitment. No differences were observed in health-related behaviors and BMI between 2010 and 2013. Conclusions: Healthy@Work ( p H@W) was either ineffective, or insufficient time had elapsed to detect a population-level change in employee lifestyle factors.